Locomotive Syndrome is a Risk Factor for the Dropout of Continuous Positive Airway Pressure Treatment in Patients with Obstructive Sleep Apnea Syndrome - Kataoka, Hiroaki (Healthcare (Basel), 2020)
Objective: The purpose of this study was to investigate the risk factors linked to patient dropout from continuous positive airway pressure (CPAP) therapy for the treatment of obstructive sleep apnea syndrome (OSAS). Methods: This study included 1191 patients with OSAS at baseline assessment, who were followed for 3 years. We evaluated clinical parameters, indicators related to OSAS treatment, exercise habits and the presence of locomotive syndrome (LS). LS was evaluated by a ‘loco-check’, as established by the Japanese Orthopedic Association. The OSAS patients were categorized at baseline as belonging to an ‘LS group’ or a ‘non-LS group’, and clinical parameters were compared. Results: Eighty-six patients (7.2%) dropped out of CPAP therapy during the 3 year follow-up period. The dropout rate of the LS group was significantly higher than that of the non-LS group. Using a Cox-proportional hazard model, the LS, old age and poor compliance were determined to be significant risk factors for dropping out of CPAP therapy. The hazard ratios (95% CI) of LS, elderly people and poor CPAP compliance were 2.11 (1.31–3.48), 1.80 (1.11–2.94) and 1.61 (1.04–2.47), respectively. Conclusion: LS may be the critical risk factor for dropping out of CPAP therapy among patients with OSAS.